ANALISIS PENGARUH KEPERCAYAAN, RELIGIUSITAS DAN KONTRIBUSI TERHADAP MINAT PEDAGANG MENGELUARKAN ZAKAT DI BAITUL MAL (STUDI KASUS PADA PEDAGANG PASAR LOS LHOKSEUMAWE) - Muhammad Yunus (Universitas Islam Negeri Sumatera Utara, 2016)
The purpose of this study to analyze the influence of trust, religiosity, and contributing to the interest of traders in Pasar Los Kota Lhokseumawe issue a zakat in Baitul Mal. The object of this research is the traders with the sampling technique using a simple random sample (sample random sampling). Samples numbered 69 merchants. Collecting data using questionnaires. Data analysis techniques with descriptive approach qualitative and quantitative analysis in linear regression. Measurements using a Likert scale with an answer from one to five.From the results if the data using regression model showed that Y = 4, 295 + 0, 406 X1 - 0.261 X2 + 0,645 X3. While the test results partially to the influence of the trust factor (X1) significantly at 4.988, greater than the value t table is 1.997 at α = 5% influence factor religiustas (X2) is 2.733, larger than the value of t is 1.997 at α = 5 % and the effect of contributing factors (X3) of 7.738, is greater than the value t table is 1.997 at a = 5%. Means partial trust factor and the contribution of each positive effect on the interest issue a zakat in the treasury, while the religiosity factor negatively affect the interests issued zakat in treasury. Each independent variable has a value of t is greater than t table on significant α = 5%.Simultaneous testing of the trust factor, religiosity can contribute to the effects of issuing zakat in treasury conducted by market traders Los town of Lhokseumawe result f calculated at 132.278 and f table 3.14. f indicate when the count is greater than f table by using an interest rate of 95 %, α = 5 % (0.05). Results of the data showed no significant effect simultaneously, then the hypothesis Ho is rejected.From these studies it can be concluded that there is influence of trust and contributing to the process of determining interest by traders in issuing zakat either partially or simultaneously testing, while for the factor of religiosity have smaller influence in determining the interest of traders in issuing treasury zakat in Lhokseumawe.